Solvation driven conformational transitions in the second transmembrane domain of mycobacteriophage holin. Issue 1 (29th January 2017) - Lella, Muralikrishna; Mahalakshmi, Radhakrishnan
ABSTRACT: Holins are pore‐forming membrane proteins synthesized by lytic phages. The second transmembrane domain (TM2) of Mycobacteriophage D29 holin presents an Ala‐ and Gly‐rich sequence, with a currently unknown structure and function. In this study, we present the spectroscopic characterization of synthetic TM2 in various solvents, detergents, and lipids. We find that TM2 adopts α‐helical conformation under conditions that promote intra‐strand hydrogen bonding, such as organic solvents and detergent micelles. When we transfer the peptide to a well‐hydrated environment, a polyproline II‐like structure is obtained. Surprisingly, we find that the polyproline II–like conformation is retained in lipid vesicles. Based on our results, we present a putative role for TM2 in the process of pore formation by holin. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 108: 1–10, 2017.